LIVE MONITORING DISTRIBUTION AS AN EFFORT TO ACHIEVE FOOD SELF-SUFFECIENCY - Vina Dwiyanti; Syifa Nur Azizah; Jelisa Zalfa Syakhisk; Aldi Palah Pamungkas; Virgantina Virgantina (Journal of Logistics and Supply Chain, 2021)
Fulfilling food needs in Indonesia faces various problems such as scarcity of food commodities, high prices, difficulty in access. These problems include the high number of food imports, so that price competition is increasingly difficult for local products. On the other hand, technological developments have entered various fields including distribution, sales, and food consumption. This challenge is an opportunity for Indonesia's food distribution to be able to meet the needs of various food commodities. This study aims to find a solution and strategy in an effort to realize Indonesia's Food Self-Sufficiency. This study uses the Literature Review method, which uses sources of scientific articles from various sources of national and international journals. The results obtained show that the Live Monitoring Distribution system can be used as an alternative tool used to determine the availability and distribution of food needs to all regions in Indonesia in real-time using three-color indications. This system can meet food needs in the right quantity, right quality, on time, and the most efficient food distribution logistics costs based on the information available in real time. Thus, the availability of food in Indonesia will be evenly distributed throughout the region and Indonesia will be able to realize the welfare of the people through Food Self-Sufficiency.